Penile Prosthesis Implantation in Patients With Peyronie's Disease: Results of the PROPPER Study Demonstrates a Decrease in Patient-Reported Depression. Issue 5 (10th April 2018) - Khera, Mohit; Bella, Anthony; Karpman, Edward; Brant, William; Christine, Brian; Kansas, Bryan; Jones, LeRoy; Kohler, Tobias; Bennett, Nelson; Rhee, Eugene; Henry, Gerard
Abstract: Background: Although there is a strong correlation between erectile dysfunction and Peyronie's disease (PD), there are limited data on the efficacy and satisfaction of inflatable penile prosthesis (IPP) placement in this population. Aim: To assess the efficacy and overall satisfaction of IPP placement in men with erectile dysfunction and concomitant PD using the Prospective Registry of Outcomes with Penile Prosthesis for Erectile Restoration (PROPPER). Methods: Data from the PROPPER study were examined to determine patient baseline characteristics and primary and secondary etiologies before IPP treatment and included type and size of implant received, presence of corporal fibrosis, and operative time. Men completed 5 validated questionnaires at baseline and annually out to 5 years. Outcomes: IPP placement was performed in 250 patients with PD with comparable surgical times and outcomes as in patients without PD. Results: 1, 180 men underwent IPP insertion at 11 sites; of these, 250 (21.2%) were diagnosed with PD. This is an ongoing study; 1- and 2-year data are available for 177 (70.8%) and 130 (52.0%) patients, respectively. Intraoperatively, 51.2% patients with PD had corporal fibrosis, with an average operative time of 52.8 minutes. At baseline, 19.3% of men (36 of 187) with PD reported being depressed, with a decrease to 10.5% (6 of 57; P  = .02) and 10.9% (5 of 46; P  = .07) at 1- and 2-year follow-ups, respectively. More than 80% of patients with PD were satisfied or very satisfied at 1- and 2-year follow-ups. In addition, more than 88% of patients with PD were using their device at the 1- and 2-year follow-up visits. Clinical Implications: Patients with concomitant PD and erectile dysfunction can safely and effectively have an IPP placed with similar outcomes as patients without PD. Strengths and Limitations: The 1st limitation was that all participating prosthetic urologists were high-volume implanters and these results might not be representative of those of general urologists. A 2nd limitation was that none of the patients were randomized. A 3rd limitation was that although most study points were mandatory, some of the data collection, including depression data, was optional, with not all sites participating. A 4th limitation was that depression data were self-reported. Conclusion: IPP can be inserted in patients with PD with acceptable patient satisfaction and usage and depressive symptoms appear to lessen in patients with PD after IPP placement.